The determinants of share prices in Zimbabwe - Sunde, Tafirenyika; Sanderson, Abel (Midlands State University, 2015)
The main thrust of the study was to establish the major determinants of stock prices in Zimbabwe. The study methodology involved the use of questionnaires and interviews Results from the study show that there are economic, political and social factors that determine stock prices in Zimbabwe. However, economic and political factors seem to be the dominant factors in the determination of stock prices. Social factors were found to be insignificant in explaining the stock prices.